How Competitive and Stable is the Commercial Banking Industry in China after Bank Reforms? - Kang H. Park (KDI Journal of Economic Policy, 2016)
This paper examines market concentration and its effect on competition in the Chinese commercial banking market. This study also investigates how changes in competition have affected the financial stability of Chinese commercial banks. To test the competitive conditions, we obtained the H statistic of the Panzar-Rosse model from a revenue function equation. The degree of financial stability is estimated by the Z-score formula. The Chinese banking industry has become an increasingly less concentrated market with an increased number of banks. Along with a decreased market concentration, competition in the Chinese banking industry has improved moderately. However, its market structure is still far from a competitive market. An individual bank's ability to earn higher markup or charge a higher net interest margin contributes to its financial soundness, although a higher degree of market concentration may have negative effect on the financial stability of the entire banking system.
Keywords: G21; L10; 330; Market concentration; Bank competition; PanzarRosse model; Bank stability; Chinese banks